The Tradition of The Grave Pilgrimage According to The Hadith of The Prophet - Muhammad Irfannuddin; Dadang Darmawan (Gunung Djati Conference Series, 2021)
This study aims to discuss the grave pilgrimage in the perspective of hadith. This research is a qualitative type which applies a literature study to interpret the opinions of ulama and hadith texts using the methods of the hadith, sociology, anthropology approach. The results and discussion of this study include the grave pilgrimage law based on the hadith of the Prophet, the views of the ulama on the grave pilgrimage law, and the procedures and etiquette in the grave pilgrimage process. This study concludes that the diversity of Muslim understanding in addressing the grave pilgrimage law can be overcome through the completion of Islamic law, but this is even more flexible approached with a cultural perspective. This study recommends further research on the hadith on the law of pilgrimage through the field study with an ethnographic analysis approach.